Sleep-patterns, sleep hygiene behaviors and parental monitoring among Bahrain-based Indian adolescents - John, Bindu (J Family Med Prim Care, 2015)
INTRODUCTION: Sleep plays an important role in adolescent's health and undergoes substantial changes with puberty and physical maturation with a preference for later bed times. Evidence shows that many adolescents are not obtaining the required amounts of sleep which is 9.25 h, due to inadequate sleep practices, academic and societal demands. This study aims at describing the (1) sleep patterns of adolescents on school days and weekends, (2) sleep hygiene practices and the extent of parental monitoring and (3) gender and grade level differences in sleep duration and sleep hygiene practices among Indian adolescents in Bahrain. MATERIALS AND METHODS: Study used a descriptive correlational design. A total of 145 adolescents from 11 to 17 years from grade 6 to 12 were selected using convenience sampling. Data was collected from November 2012 to March 2013. A structured questionnaire for sleep patterns and Mastin et al.'s Sleep Hygiene Index for assessing sleep hygiene practices were used. RESULTS: The adolescents’ total sleep duration was 7.07 ± 1.13 hours. A highly significant difference in sleep duration on school days and weekends between adolescents of various grade levels (P < 0.001 and 0.001, respectively) and between parental monitoring at the time of getting up on school days and sleep duration (P value 0.026 at 0.05 level of significance) was found. Gender was not significant with the sleep duration, and also with Sleep Hygiene Index scores. CONCLUSION: The results suggest that there is a high prevalence of insufficient sleep and irregular bed-time schedule among Indian adolescents in Bahrain. Interventions directed toward improving sleep and promoting good sleep hygiene strategies are required to improve the physical and emotional health of adolescents.